1998
DOI: 10.1021/jp982311q
|View full text |Cite
|
Sign up to set email alerts
|

CHF2Cl and CH3CF2Cl Detection by Coherent Anti-Stokes Raman Scattering and Photoacoustic Raman Spectroscopy

Abstract: The coherent anti-Stokes Raman scattering (CARS) and photoacoustic Raman spectroscopy (PARS) spectra of gaseous CHF 2 Cl and CH 3 CF 2 Cl in the 3000 cm -1 region are reported for the first time. Several vibrational bands are observed related to C-H stretch fundamentals of CHF 2 Cl isotopomers, and to CH 3 stretches and the first overtone of CH 3 deformation of CH 3 CF 2 Cl. The simultaneous detection of CARS/PARS signals aids the assignment of the isotopomer bands. Both methods are appropriate for detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Nonlinear change of refractive index gives rise to filamentation (recent reviews of this broad topic can be found in [1,2]), whereas spatially localized heating results in the formation of acoustic waves [3][4][5][6][7][8] and long-lived gas density perturbations [9][10][11]. Photo-acoustic vibrational Raman spectroscopy has been successfully utilized for chemical detection and trace analysis [12,13].…”
mentioning
confidence: 99%
“…Nonlinear change of refractive index gives rise to filamentation (recent reviews of this broad topic can be found in [1,2]), whereas spatially localized heating results in the formation of acoustic waves [3][4][5][6][7][8] and long-lived gas density perturbations [9][10][11]. Photo-acoustic vibrational Raman spectroscopy has been successfully utilized for chemical detection and trace analysis [12,13].…”
mentioning
confidence: 99%
“…Several low resolution studies of the infrared [13][14][15][16] and Raman spectra [13,14,17] of HCFC-142b have been reported and the assignment of the vibrational modes has been established by harmonic force field calculations [15,18,19]. The exact wavenumber of the lowest vibrational band, the torsional mode m 18 is still uncertain.…”
Section: Methodsmentioning
confidence: 99%
“…Several low-resolution studies of the infrared (2-5) and Raman spectrum (2,3,6) of DFCE have been reported, and the assignment of the vibrational fundamentals has been supported by ab initio calculations of the harmonic force field at different levels of theory (4,7,8).…”
Section: Introductionmentioning
confidence: 93%